HOUSEKEEPING GENES ANALYSIS OF FOODBORNE PATHOGENIC BACTERIA Vibrio parahaemolyticus ISOLATED FROM AQUATIC BIRDS IN THAILAND - Eakapong Tamboon; Peeraya Ekchariyawat; Orasa Suthienkul; Chonchanok Muangnapoh (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Vibrio parahaemolyticus is one of the leading causative agent of foodborne disease. Infection is caused by consumption of undercooked contaminated seafood. V. parahaemolyticus is commonly found in crustacean species and marine environment. Presence of this organism in avian host has been previously reported, however genetic analysis of avian V. parahaemolyticus is required for molecular epidemiological study of this organism. The aim of this study was to determine genetic profile of V. parahaemolyticus isolated from fecal aquatic bird samples by modified Multilocus Sequence Typing (MLST) method. Methods: Three housekeeping genes fragments (dnaE, gyrB and pntA) of total 18 V. parahaemolyticus isolates from fecal aquatic bird samples at Bangpoo resort, Samut Prakarn province, Thailand, during 2016-2017, were amplified by using conventional PCR for nucleotide sequencing. Nucleotide sequences were analyzed and phylogenetic tree were constructed by MEGA 7.0 software. Comparative genetic analysis of avian isolates from Thailand and worldwide isolates were performed by using information from MLST database of V. parahaemolyticus ( https://pubmlst.org /vparahaemolyticus/). Results: Three housekeeping genes of 18 isolates were successfully amplified and purified for nucleotide sequencing. Phylogenetic tree analysis of concatenated nucleotide sequences indicated that 18 Thai avian isolates were genetically diverse. Five isolates (MUVP 9, 11, 22, 23 and 24) represented identical genetic profile with clinical isolates from China, India, Japan and Peru. Other examined isolates were closely related to environmental isolates from China and United Kingdom. These results showed that aquatic birds are natural reservoir of V. parahaemolyticus strains with multiple genetic background. Conclusion: This study indicated that aquatic birds possessed potentially pathogenic V . parahaemolyticus and may play a role in transmission of this organism across the countries.